British Cardiovascular Society survey of the provision and structure of cardiology multidisciplinary meetings in England - B. Liu; R.A. Archbold; J.P. Greenwood; S. Ray; S.S. Hothi (Clinical Medicine)
Multidisciplinary meetings (MDMs) are central to clinical decision-making in many areas of cardiology. This study assessed current provision and structure of cardiology MDMs in England in comparison with national guidelines.British Cardiovascular Society (BCS) members were surveyed regarding frequency, core attendees, and organisational aspects of cardiology MDMs for myocardial revascularisation, endocarditis, heart failure, aortic valve, mitral and tricuspid valve MDMs, whether local, regional or outside of the region. Access to electrophysiology (EP), inherited cardiac conditions, and adult congenital heart disease (ACHD) MDMs was also assessed.Survey responses were received from 64 hospitals across England, of which 40 (62%) were secondary care centres and 24 (38%) were tertiary care centres. All units had access to revascularisation MDMs, although 6% of them (all in secondary care centres) lacked any surgical representation. Heart failure MDMs were available in 94% of centres, but 7% reported no attendance by a cardiologist with specialist interest in heart failure, and 23% reported no attendance by a device specialist. 61% of centres had access to dedicated endocarditis MDMs; however, 11% were not attended by a microbiologist or infectious disease physician, and 22% were not attended by a surgeon. Aortic valve MDMs were available in 69% of centres, while mitral and tricuspid valve MDMs were available in 56% of centres. One quarter of centres reported no access to EP, and one third of centres reported no access to ICC or ACHD MDMs.Substantial improvements in provision and structure of cardiology MDMs in England are needed in order to meet national guidance.